Synthesis, Characterization and X-Ray Diffraction Studies of Co(II), Ni(II), Cu(II) and Zn(II) Complexes with Schiff Base Derived from 5-nitrosalicylaldehyde and Anthranilic Acid - MEHTA, B.H.; MORE, P.S. (Asian Journal of Chemistry, 2010)
Transition metal (II) complexes of the type ML·nH2O [where M−Co(II), Ni(II), Cu(II) and Zn(II), L-Schiff base derived from 5-nitro salicylaldehyde and anthranilic acid, n=0,1...] have been prepared and characterized by elemental analysis, molar conductivity, IR, electronic spectra, magnetic susceptibility studies and X-ray difraction spectra. Molar conductivity measurements indicate that the complexes are non-electrolytic in nature. From the analytical and spectral data, the stoichiometry of the complexes has been found to be 1:1 (metal : ligand). IR spectral data suggests that the ligand behaves as a monobasic tridentate ligand with O:N:O donor sequence towards metal ions. Magnetic susceptibility measurements indicate paramagnetic behaviour of all the complexes except Zn-complex. X-ray diffraction studies suggest monoclinic crystal system for these complexes.